CONTROL OF EDUCATIONAL ACHIEVEMENTS OF MATHEMATICAL DISCIPLINES OF FUTURE ECONOMISTS - Proshkin, Vladimir V.; Gribonos, Yevgenia U. (Educological discourse, 2016)
The article presents the control system of future economists’ educational achievements in the process of studying mathematical disciplines, which aims at improving students’ quality of mathematical preparation and includes the following components: substantive, functional, managerial and technological. Peculiarities of the program application "OpenTEST" for testing students have been examined. It has also been presented the structure of the information packages on mathematical disciplines to ensure transparency of the educational process and maximum awareness of future specialists according to all aspects of the organization and control. Requirements for individual tasks development system and methodical materials of practice and oriented nature for students’ independent work have been described. Further researches prospects which are connected with system control introduction of future economists’ educational achievements during studying mathematical disciplines have been presented.